Embryonic brain extract induces collagen biosynthesis in cultured muscle cells: involvement in acetylcholine receptor aggregation. - Kalcheim, C (1982)
The involvement of extracellular matrix components in induction of the aggregation of acetylcholine (AcCho) receptors by factor(s) present in embryonic brain extract was investigated. Embryonic brain extract induced a three-fold increase in the number of AcCho receptor aggregates on the surface of cultured myotubes and a 5- to 10-fold increase in the synthesis of procollagen, which was secreted into the medium and converted to collagen. Adult brain extract, embryonic serum, and embryonic liver extract were less active in stimulating both collagen synthesis and AcCho receptor aggregation. A physiological connection between the two processes is suggested, since the number of AcCho receptor aggregates could be reduced to control levels by treating brain extract-stimulated myotubes with purified bacterial collagenase. In addition, stimulation of collagen secretion by ascorbic acid (50 micrograms/ml) promoted a 1.6-fold increase in AcCho receptor aggregation. When ascorbic acid was added together with the brain extract, further increases in both collagen synthesis and AcCho receptor aggregation were observed.